2007
DOI: 10.1007/s10764-007-9136-6
|View full text |Cite
|
Sign up to set email alerts
|

Population Size and Characteristics of Alouatta pigra Before and After a Major Hurricane

Abstract: Although some environmental risks and resources are known to affect the evolution of primate social groups, we know little about the effect of major natural disturbances on primate populations. Hurricane Iris hit the Monkey River watershed in southern Belize in October 2001, presenting a unique opportunity to document the effects of a natural disaster under circumstances wherein some pre-hurricane data were available. We measured the characteristics of the population of black howlers in the affected forest 3.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(60 citation statements)
references
References 48 publications
1
57
0
2
Order By: Relevance
“…Returning to the issue of ecological density, in Belize Ostro et al [2001] and Pavelka et al [2007] have suggested that high densities are owing to the frequent occurrence of multimale and multifemale social units as opposed to unimale or other types of social units. However, even though this social unit was also very frequent in Balancán, ecological densities in Balancán were much lower.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Returning to the issue of ecological density, in Belize Ostro et al [2001] and Pavelka et al [2007] have suggested that high densities are owing to the frequent occurrence of multimale and multifemale social units as opposed to unimale or other types of social units. However, even though this social unit was also very frequent in Balancán, ecological densities in Balancán were much lower.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, we might predict changes in demography and distribution, including troop fission, troop migrations, expulsions of both sexes, death of both adults and immature individuals, and eventually a decrease in overall abundance [Brockett et al, 2000;Crockett & Eisenberg, 1987;Ostro et al, 2001;Pavelka et al, 2003Pavelka et al, , 2007.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cecropia peltata is widespread throughout the neotropics and, as a shade-intolerant pioneer species, is most abundant in disturbed and open areas. Cecropia peltata is particularly important in the diet of the Monkey River black howler population because the forest was severely damaged by Hurricane Iris in 2001 (Pavelka et al, 2003(Pavelka et al, , 2007.…”
mentioning
confidence: 99%
“…When a group was heard vocalising we estimated the distance in metres and direction of the group. In previous studies (Pavelka et al, 2007), we found this overestimated the distance by 0.5 to 1.0 km, therefore we took this into account in our analysis here. All spatial data (visual and vocal contacts, confirmations of presence from local informants, and track information) were entered into ArcMap software (v.10.1).…”
Section: Forest Characteristics Associated With a Pigramentioning
confidence: 91%